Transdisciplinarity among universities as a catalyst for a gender-sensitive revolution. Strategies and approaches from the perspective of communication design - Francesca Casnati; Valeria Bucchetti (Feminismo/s, 2024)
One of the most influential and proven vehicles for sustainable development is inclusive and quality education. This is why it is crucial to promote gender equality in higher education and research, for only in this way can we build a fairer world where everyone has equal opportunities to contribute, create, fulfil their dreams, use their talents, and above all, develop a more sustainable world in collaboration with other human beings. This contribution intends to approach the issue of the university’s role in closing the gender gap from the disciplinary perspective of Communication Design. The contribution therefore aims to fuel the reflection on the role and strategies that the educational path in design can experiment and equip itself with to promote a shift in perspective and contribute to a positive change. The presentation of the case study «A multidisciplinary awareness-raising campaign project against gender-based violence, from the university for the university» has the aim of supporting the argumentation. The case study constitutes a practical example of an inter-university multidisciplinary project, an awareness-raising campaign, in which the synergy and juxtaposition of different and complementary disciplines enable the activation of a virtuous circle of knowledge and awareness. The strategy implemented in this case involved the university on several intertwining levels: from the university, through the university, for the university. The actors engaged in the research and project were located at different levels of the academic pathway: Professors, researchers and students worked together and with different roles in the various stages of the project